2007
DOI: 10.1210/en.2007-0339
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming: Follicular Persistence in Prenatal Testosterone-Treated Sheep Is Not Programmed by Androgenic Actions of Testosterone

Abstract: Testosterone (T) treatment during early-midgestation (30-90 d; term is 147 d) leads to reproductive cycle defects. Daily ultrasonography in prenatal T-treated female sheep during the first two breeding seasons revealed an increase in the number of large follicles and follicular persistence. The objective of this study was to determine whether follicular persistence in prenatal T-treated females was programmed by the androgenic actions of T. Pregnant Suffolk ewes were injected with 100 mg (im; twice weekly) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 46 publications
6
88
3
1
Order By: Relevance
“…Therefore we focused our attention on the role of androgens within a critical window of porcine fetal ovarian development. In prenatal testosterone-treated sheep, the consequences of elevated androgen level (polycystic ovarian morphology, enhanced follicular recruitment/depletion and increased estradiol secretion) were observed in Flutamide affects folliculogenesis in fetal pig adulthood (Steckler et al 2007). The excess of prenatal androgens disrupted the expression of ovarian steroid receptor protein, altering the ovarian developmental trajectory and causing an imbalance in AR/estrogen receptor (ER) protein in sheep (Ortega et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore we focused our attention on the role of androgens within a critical window of porcine fetal ovarian development. In prenatal testosterone-treated sheep, the consequences of elevated androgen level (polycystic ovarian morphology, enhanced follicular recruitment/depletion and increased estradiol secretion) were observed in Flutamide affects folliculogenesis in fetal pig adulthood (Steckler et al 2007). The excess of prenatal androgens disrupted the expression of ovarian steroid receptor protein, altering the ovarian developmental trajectory and causing an imbalance in AR/estrogen receptor (ER) protein in sheep (Ortega et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The excess of prenatal androgens disrupted the expression of ovarian steroid receptor protein, altering the ovarian developmental trajectory and causing an imbalance in AR/estrogen receptor (ER) protein in sheep (Ortega et al 2009). Moreover, female rhesus monkeys (Abbott et al 1998), sheep (Steckler et al 2007), mice (Sullivan & Moenter 2004) and rats (Foecking et al 2005) prenatally exposed to either testosterone or dihydrotestosterone (DHT) exhibited disorders in the ovulatory cycles in adulthood. The androgen excess phenotypes resemble those of women with polycystic ovary syndrome (PCOS), suggesting a fetal origin of PCOS (Abbott et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Excess prenatal exposure to testosterone or TP leads to irregular cycling and oligo-or anovulation in adult ewes (Clarke et al 1976), with the severity of disruption higher in females treated earlier in gestation (days 30-80), than in those exposed later (Clarke et al 1977, Savabieasfahani et al 2005. Prenatal treatment with testosterone or TP in ewes between the days of 30-90 of gestation induces the PCOS ovarian characteristics of increased ovarian weight (West et al 2001, Forsdike et al 2007, polycystic ovaries (West et al 2001, Forsdike et al 2007, increased follicular recruitment (Clarke et al 1977, West et al 2001, Smith et al 2009) and increased presence of large antral follicles (Manikkam et al 2006, Steckler et al 2007. However, other studies failed to observe an increase in ovarian weight (Smith et al 2009, Hogg et al 2012) and numbers of growing follicles (preantral and/or antral) (Hogg et al 2012).…”
Section: Testosteronementioning
confidence: 99%
“…The key PCOS characteristics of cycle irregularity and ovulation disruption (Steckler et al 2007) have been reported in ewes prenatally exposed to excess DHT on days 30-90 of gestation, but features such as the classic polycystic ovary appearance (Smith et al 2009) and increased ovarian weight (West et al 2001) are not displayed. Interestingly, while prenatal testosterone exposure increased the number of large antral follicles and follicular persistence in one study, prenatal DHT exposure only increased the number of small growing follicles, but not the number of large antral follicles (Steckler et al 2007). Furthermore, in another study, while prenatal testosterone was found to increase follicle recruitment, prenatal DHT did not do so (Smith et al 2009).…”
Section: Dihydrotestosteronementioning
confidence: 99%
“…Srinivasan [27]. Prenatal exposure to androgen excess can lead to, as adults, disrupted ovarian cycles and abnormalities of early follicle development that mimic those observed in women with polycystic ovary syndrome [28][29][30][31]. It was reported that environmental factors can affect spermatogenesis at the level of germ and Stertoli cells and the composition of seminal fluid [32,33].…”
Section: Discussionmentioning
confidence: 99%